MXene / carbon composites, methods of making the same, wave-absorbing uses, films, coatings, paints

CN118164487BActive Publication Date: 2026-10-23济南三川新材料科技有限公司 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410292826.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2026-10-23
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

[0004]本发明的目的在于针对现有技术中MXene/碳复合材料制备过程复杂,能耗大,成本高的问题,提出一种基于碳材料气相生长MXene,得到MXene/碳复合材料的方法及其在吸波领域的应用

Benefits of technology

[0024]本发明的MXene/碳复合材料中的MXene材料基于碳材料表面生长得到,避免了常规MXene/碳复合材料制备复杂的工艺,同时也解决了常规MXene材料易堆叠和高密度的问题。特别地,本发明的制备方法中原料易于获取,方法简单,能够在开放体系中合成,适用于工业化宏量制备,具有工业实用性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118164487B_ABST
    Figure CN118164487B_ABST
Patent Text Reader

Abstract

The application discloses a MXene / carbon composite material and a preparation method, wave-absorbing application, film, coating and paint thereof; wherein the preparation method of the MXene / carbon composite material comprises the following steps: heating a single substance of a transition metal, a carbon material and a halogen hydride or halogen single substance gas to a reaction temperature and keeping the temperature for a predetermined time, so that MXene is grown on the carbon material, and the MXene / carbon composite material is obtained. The preparation method avoids the complex process of conventional MXene / carbon composite material preparation, and solves the problems of easy stacking and high density of conventional MXene material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of microwave absorbing materials, and mainly relates to an MXene / carbon composite material and its preparation method, microwave absorbing applications, thin films, coatings, and paints. Background Technology

[0002] Emerging wireless communication technologies, exemplified by 5G, while driving social progress, have also exacerbated electromagnetic pollution. Therefore, developing high-performance microwave absorbing materials with characteristics of being thin, lightweight, wide-area, and strong is crucial. Two-dimensional transition metal carbide / nitride (MXene) materials, with their excellent conductivity, high specific surface area, and abundant functional groups, have become a highly promising microwave absorbing material. However, addressing the impedance mismatch, easy stacking, and high density issues inherent in MXene materials remains a critical challenge.

[0003] Currently, various materials, such as metal oxides, polymers, and carbon materials, are typically selected and combined with MXene to optimize microwave absorption performance. Taking MXene / C composite materials as an example, Professor Sun Zhengming's research group at Southeast University (Nano-Micro Letters (2023) 15: 194) designed an MXene / C composite material by combining two-dimensional MXene materials with polyacrylonitrile (PAN) fibers and then carbonizing them using electrospinning technology. Currently, the MXene components in these reported composite materials are all obtained through pre-preparation. The preparation of MXene materials typically involves etching the A atoms in the MAX phase ceramic material with an etchant (HF acid or hydrochloric acid and metal fluoride salt). This process involves immersing the MAX ceramic material in the etching solution for up to 24 hours, which is not only very time-consuming but also generates a large amount of hazardous waste. Furthermore, subsequent processes such as ultrasonic exfoliation, liquid-phase cleaning, and drying are required. In addition, the preparation of the precursor MAX phase ceramic material requires high-temperature, long-term sintering. This results in the complexity, high energy consumption, and high cost of MXene / C material preparation, making industrial production difficult and hindering its further application. Summary of the Invention

[0004] The purpose of this invention is to address the problems of complex, energy-intensive, and costly preparation processes of MXene / carbon composite materials in existing technologies, and to propose a method for obtaining MXene / carbon composite materials based on the vapor-phase growth of MXene from carbon materials, as well as its application in the field of microwave absorption.

[0005] The first aspect of the present invention provides a method for preparing an MXene / carbon composite material, comprising: heating a transition metal element, a carbon material, and a halide hydride or a halide gas to a reaction temperature and holding the temperature for a predetermined time, so that MXene grows on the carbon material to obtain the MXene / carbon composite material.

[0006] In some embodiments, the carbon material is selected from one or more of natural graphite, flake graphite, expanded graphite, graphene, and carbon fiber.

[0007] In some embodiments, the transition metal is selected from one or more of Ti, V, Ta, W, Zr, and Mo.

[0008] In some embodiments, the hydrogen halide gas is selected from HCl, HBr, or HI.

[0009] In some embodiments, the halogen gas is selected from Cl2, Br2 or I2.

[0010] In some embodiments, the reaction temperature is between 650 and 850°C.

[0011] In some embodiments, the aforementioned heat preservation time is between 1 minute and 24 hours.

[0012] In some embodiments, the chemical formula of the above-mentioned MXene is M2XT. x Or M2X, where M represents a transition metal element; X represents carbon, and T represents... x The surface represents a surface containing functional groups, including at least one of Cl, Br, and I.

[0013] In some embodiments, the solid product obtained after the reaction is dispersed in a non-aqueous solvent, and impurities are separated by precipitation or centrifugation; preferably, the non-aqueous solvent is selected from one or more of propylene carbonate, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, N,N-dimethylformamide, N-methylformamide, and isopropanol.

[0014] In some embodiments, the carbon material described above is selected from graphite.

[0015] In some embodiments, the aforementioned transition metal element is titanium powder.

[0016] In some embodiments, the above-mentioned halogenated hydride is hydrogen chloride.

[0017] A second aspect of the present invention provides an MXene / carbon composite material obtained by the above preparation method.

[0018] In some embodiments, the mass content of carbon material in the above-mentioned MXene / carbon composite material is between 1% and 99%.

[0019] A third aspect of the present invention provides the use of the above-mentioned MXene / carbon composite material for microwave absorption.

[0020] A fourth aspect of the present invention provides a microwave absorbing film comprising: an MXene / carbon composite material obtained by the above preparation method.

[0021] A fifth aspect of the present invention provides a coating comprising: an MXene / carbon composite material obtained by the above preparation method.

[0022] A sixth aspect of the present invention provides a coating in which the above-mentioned MXene / carbon composite material is added.

[0023] A seventh aspect of the present invention provides an electronic device in which the above-described absorbing film or coating is disposed.

[0024] The MXene material in the MXene / carbon composite material of this invention is obtained by growing on the surface of carbon material, avoiding the complex process of conventional MXene / carbon composite material preparation, and also solving the problems of easy stacking and high density of conventional MXene materials. In particular, the raw materials in the preparation method of this invention are readily available, the method is simple, it can be synthesized in an open system, it is suitable for industrial-scale preparation, and has industrial applicability.

[0025] As a microwave absorbing material, the MXene / C composite material of this invention uses carbon materials (such as graphite and carbon fiber) as the matrix. These matrix carbon materials themselves have excellent thermal conductivity, and the resulting MXene / C composite material can retain the thermal conductivity of the matrix, meeting the needs of modern electronic devices in terms of electromagnetic interference prevention and heat dissipation. Attached Figure Description

[0026] Figure 1 The target product Ti2CT in Embodiment 1 of the present invention x XRD pattern of MXene / carbon.

[0027] Figure 2 The target product Ti2CT in Embodiment 1 of the present invention x (a) SEM image of MXene / carbon; (b) TEM image; (c) HRTEM and FFT image.

[0028] Figure 3 The target product Ti2CT in Embodiment 1 of the present invention x (a) SEM image of MXene / carbon; (b) Ti element; (c) C element; (d) Cl element distribution map.

[0029] Figure 4 The target product Ti2CT in Embodiment 1 of the present invention x Microwave absorption performance of MXene / carbon.

[0030] Figure 5 The target product Ti2CT in Embodiment 2 of the present invention x XRD pattern of MXene / carbon.

[0031] Figure 6The target product Ti2CT in Embodiment 2 of the present invention x (a) SEM image of MXene / carbon; (b) TEM image; (c) HRTEM and FFT image.

[0032] Figure 7 The target product Ti2CT in Embodiment 2 of the present invention x (a) SEM image of MXene / carbon; (b) Ti element; (c) C element; (d) Cl element distribution map.

[0033] Figure 8 The target product Ti2CT in Embodiment 2 of the present invention x Microwave absorption performance of MXene / carbon.

[0034] Figure 9 The target product Ti2CT in Embodiment 3 of the present invention x XRD pattern of MXene / carbon.

[0035] Figure 10 The target product Ti2CT in Embodiment 3 of the present invention x SEM image of MXene / carbon.

[0036] Figure 11 The target product Ti2CT in Embodiment 3 of the present invention x (a) SEM image of MXene / carbon; (b) Ti element; (c) C element; (d) Cl element distribution map.

[0037] Figure 12 The target product Ti2CT in Embodiment 3 of the present invention x Microwave absorption performance of MXene / carbon. Detailed Implementation

[0038] Example 1 This embodiment provides an MXene / carbon composite material and its preparation method, comprising the following steps: heating titanium powder, flake graphite powder, and hydrogen chloride gas (HCl) to a reaction temperature and holding at that temperature for a predetermined time, thereby growing MXene on graphite to obtain the MXene / carbon composite material. More specific preparation steps include: Step 1) Weigh 600mg of titanium powder and 25mg of flake graphite and place them in a magnetic boat and put it into a tube furnace. Introduce argon gas into the tube furnace. Set the heating program of the tube furnace to increase the temperature to the reaction temperature of 850 degrees Celsius at a rate of 20°C / min. Argon gas is used as a protective gas during the heating process. Step 2) When the temperature reaches the preset temperature of 850 degrees, hydrogen chloride gas is introduced into the tube furnace so that the volume fraction of hydrogen chloride gas is 10%, and the temperature is maintained for 12 hours to carry out the gas phase growth reaction. Step 3) After the set holding time, change the gas flow into the tube furnace back to argon, open the lid and air cool to room temperature, then remove the product from the magnetic boat. Step 4) Take out the solid product, grind it for 5 minutes, wash it with deionized water, and dry it to obtain the target product.

[0039] The product was analyzed by X-ray diffraction (XRD), and the results are as follows: Figure 1 As shown, the XRD pattern is similar to that of Ti2CCl2MXene obtained by Lewis acid molten salt etching of the Ti2AlC MAX phase, with a strong diffraction peak appearing at around 6.4 degrees, corresponding to Ti2CT. x The diffraction peaks of the MXene (002) crystal plane indicate that Ti2CT was successfully prepared by growth using titanium powder, flake graphite, and hydrogen chloride gas. x The XRD pattern of the MXene product still shows a characteristic peak of C at 26°, indicating that the product is an MXene / C composite material. Furthermore, the XRD pattern shows that the solid product does not contain characteristic peaks of titanium powder, indicating that the titanium powder fully participated in the reaction. The reaction system of this invention is an open system; during the reaction, excess titanium powder is converted into TiCl4 or TiCl3 and expelled from the system as a gas.

[0040] Cubic TiC in the product z ( z = 0.5~1) is a byproduct, which can be effectively removed by adding the solid product to a non-aqueous solvent for re-precipitation or by centrifugation. In this invention, the non-aqueous solvent can be selected from one or more of propylene carbonate (PC), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), acetonitrile (ACN), N,N-dimethylformamide (DMF), N-methylformamide (NMF), and isopropanol (IPA).

[0041] In this embodiment, the solid product was added to the non-aqueous solvent DMF and sonicated. After sonication for 1 hour, the sonicated dispersion was centrifuged at 3000 rpm for 5 minutes. Then, the upper dispersion was centrifuged at 1000 rpm for 10 minutes. The bottom product was collected and dried to obtain the purified MXene / C composite material.

[0042] The MXene of this invention is based on carbon material surface growth. By controlling the gas-phase reaction conditions, such as reaction temperature or time, the mass content of C in the composite material can be adjusted. In other embodiments, the heating reaction temperature is between 650°C and 900°C, and the holding time is between 10 min and 24 h.

[0043] The products were analyzed by scanning electron microscopy (SEM), and the results are as follows: Figure 2As shown in (a), an accordion-like layered structure of MXene Ti2CT can be observed in the MXene / C composite material. x . Figure 2 (c) shows the HRTEM image and the diffraction spots obtained by FFT. The product exhibits a hexagonal crystal structure, consistent with the reported structure of MXene, and consistent with the XRD and SEM analysis results. EDS analysis reveals the elemental distribution of Ti, C, and Cl in this two-dimensional nanosheet. Figure 3 (b), (c) and (d) indicate that the target product obtained is Ti2CT containing Cl functional groups. x MXene / C composite material.

[0044] This embodiment also provides a method for using the above-mentioned Ti2CT. x The application of MXene / C composite material as a microwave absorbing material, and the resulting target product Ti2CT x The absorption performance of MXene / C was tested, and the results are as follows: Figure 4 As shown, the highest reflection loss is -45.6 dB at a thickness of 2.75 mm.

[0045] In this invention, the carbon material is more preferably graphite. When graphite is used as the carbon material matrix, the resulting MXene / C composite material exhibits higher reflection loss, which may be related to the fact that graphite has higher crystallinity and better thermal conductivity.

[0046] Example 2 This embodiment provides an implementation method for MXene / carbon composite materials, similar to Example 1, except that the carbon material in this embodiment is expanded graphite powder. The specific preparation steps include: Step 1) Mix Ti powder and expanded graphite at a mass ratio of 24:1 and grind them thoroughly until uniform. Weigh 2425mg and place it in a magnetic boat, then place it in a tube furnace and introduce argon gas into the tube furnace. Step 2) Set the heating program of the tube furnace to increase the temperature to the reaction temperature of 800 degrees Celsius at a rate of 20°C / min, with argon gas used as a protective gas during the heating process; Step 3) When the temperature reaches the preset temperature of 800 degrees, hydrogen chloride gas is introduced into the tube furnace so that the volume fraction of hydrogen chloride gas is 10%, and the temperature is maintained for 16 hours to carry out the gas phase growth reaction. Step 4) After the set holding time, change the gas flow into the tube furnace back to argon, open the lid and air cool to room temperature, then remove the product from the magnetic boat. Step 5) Take out the solid product, grind it for 5 minutes, wash it with deionized water, and dry it to obtain the target product.

[0047] The product was analyzed by X-ray diffraction (XRD), and the results are as follows: Figure 5 As shown, the XRD pattern is similar to that of Ti2CCl2MXene obtained by Lewis acid molten salt etching of the Ti2AlC MAX phase, with a strong diffraction peak appearing at around 6.7 degrees, corresponding to Ti2CT. x The diffraction peaks of the MXene (002) crystal plane indicate that Ti2CT was successfully prepared by growth using titanium powder, expanded graphite, and hydrogen chloride gas. x The XRD pattern of the MXene product also shows a characteristic peak of C at 26°, indicating that the product is an MXene / C composite material. The product contains cubic TiC. z ( z = 0.5~1) is a by-product that can be effectively removed by precipitation from the non-aqueous dispersion of the raw material product.

[0048] The products were analyzed by scanning electron microscopy (SEM), and the results are as follows: Figure 6 As shown in (a), the comparison reveals that MXeneTi2CCl x It exhibits an accordion-like layered structure, consistent with the morphology of reported MXene. EDS analysis revealed the elemental distribution of Ti, C, and Cl in this two-dimensional nanosheet. Figure 7 (b), (c), and (d) indicate that the target product obtained is the MXene material Ti2CT containing Cl functional groups. x This indicates that the target product obtained is Ti2CT containing Cl functional groups. x MXene / C composite material. The target product, MXene Ti2CT, was obtained. x / C was used to test the absorption performance, and the results are as follows Figure 8 As shown, the highest reflection loss is -20.4 dB at a thickness of 2.82 mm.

[0049] Example 3 This embodiment provides another implementation of the MXene / carbon material, similar to Embodiment 1, except that the carbon material in this embodiment is carbon nanofibers. The specific preparation steps include: Step 1) Mix Ti powder and carbon nanofibers at a mass ratio of 16:1 and grind them thoroughly until uniform. Weigh 1625mg and place it in a magnetic boat. Put the boat into a tube furnace and introduce argon gas into the tube furnace. Step 2) Set the heating program of the tube furnace to increase the temperature to the reaction temperature of 850 degrees at a rate of 20°C / min, with argon as the protective gas during the heating process; Step 3) When the temperature reaches the preset temperature of 850 degrees, hydrogen chloride gas is introduced into the tube furnace so that the volume fraction of hydrogen chloride gas is 10%, and the temperature is maintained for 3 hours to carry out the gas phase growth reaction. Step 4) After the set holding time, change the gas flow into the tube furnace back to argon, open the lid and air cool to room temperature, then remove the product from the magnetic boat. Step 5) Take out the solid product, grind it for 5 minutes, wash it with deionized water, and dry it to obtain the target product.

[0050] The product was analyzed by X-ray diffraction (XRD), and the results are as follows: Figure 9 As shown, the XRD pattern is similar to that of Ti2CCl2MXene obtained by Lewis acid molten salt etching of Ti2AlC MAX phase, with a diffraction peak appearing at around 5 degrees, corresponding to Ti2CT. x The diffraction peaks of the MXene (002) crystal plane indicate that Ti2CT was successfully prepared by growth using titanium powder, carbon nanofibers, and hydrogen chloride gas. x MXene. XRD peaks of carbon nanofibers are also present.

[0051] The product was tested by scanning electron microscopy (SEM), and the results are as follows: Figure 10 As shown in the comparison, MXene Ti2CT x The nanosheets are grown in a carpet-like pattern on carbon nanofibers. EDS analysis reveals the distribution of Ti, C, and Cl elements within these two-dimensional nanosheets. Figure 11 (b), (c) and (d) indicate that the target product obtained is Ti2CT containing Cl functional groups. x MXene / C composite material. The target product Ti2CT was obtained. x The absorption performance of MXene / C was tested, and the results are as follows: Figure 12 As shown, the highest reflection loss is -34.5 dB at a thickness of 2.33 mm.

[0052] The thickness of the absorbing film or coating of the present invention is preferably 2 to 3 mm.

[0053] The mechanism of synthesizing MXene / carbon composite material by vapor phase growth in this invention may be that transition metal powder reacts with hydrogen halide or halogen elemental gas with solid carbon material at high temperature, and MXene material is formed by vapor phase deposition on the surface of carbon material, thus obtaining carbon / MXene composite material with carbon material as matrix.

[0054] In other embodiments, the transition metal powder may be replaced with other types, such as one or more of Ti, V, Ta, W, Zr, and Mo. These transition metal elements react with hydrogen halides or halogens to generate transition metal halides. These chlorides react with carbon materials under high temperature conditions to generate MXene materials with halogen functional groups.

[0055] Example 4 This embodiment provides another MXene / carbon composite material, similar to Example 1, except that titanium powder is replaced with vanadium (V) powder, and the mixture is heated to 800 degrees Celsius and held for 12 hours to obtain V2CCl. x MXene / carbon composite material.

[0056] Example 5 This embodiment provides another MXene / carbon composite material, similar to Example 1, except that HCl is replaced with chlorine (Cl2), and the mixture is heated to 850 degrees Celsius and held at that temperature for 12 hours to obtain Ti2CCl. x MXene / carbon composite material.

[0057] Example 6 This embodiment provides another MXene / carbon composite material, similar to Example 1, except that HCl is replaced with HI, and the material is heated to 750 degrees Celsius and held for 12 hours to obtain Ti₂CI. x MXene / carbon composite material.

[0058] The preferred embodiment of the application of the MXene / C composite material of the present invention as a microwave absorbing material is to add it as a functional additive to a coating to obtain a coating with microwave absorbing function.

[0059] As a microwave absorbing material, the MXene / C composite material of this invention avoids the complex manufacturing process of conventional MXene materials because MXene is grown on the surface of carbon materials. It also solves the problems of easy stacking and high density associated with conventional MXene materials. The trend towards high integration and thinness in electronic devices makes it more difficult to simultaneously add microwave absorbing and thermally conductive materials within a limited space. The MXene / C composite material of this invention uses carbon materials (such as graphite and carbon fiber) as the matrix. Compared to carbon materials formed by carbonizing polymers (such as PAN), the carbon matrix materials of this invention inherently possess excellent thermal conductivity. The resulting MXene / C composite material retains the thermal conductivity of the matrix, meeting the needs of modern electronic devices in terms of electromagnetic interference protection and heat dissipation.

[0060] As can be seen from the above embodiments, the raw materials for the preparation method of the present invention are mainly transition metal powder, carbon materials, and hydrogen halide gas or halogen gas. These raw material components are all conventional chemical products, which are easy to obtain and inexpensive. The reaction process of the present invention is carried out in an open system without the need for sealing or sealing. The gaseous raw materials or products can enter or exit the reaction system. This development system is suitable for industrial-scale preparation and improves the preparation efficiency. Compared with the conventional MXene preparation, which requires high-temperature sintering to form a MAX phase (~1500℃) and then MXene synthesis by etching and cleaning the MAX phase, the reaction process of the present invention can be carried out in a relatively low-temperature environment (650 to 850℃) to deposit and grow MXene on carbon materials. The one-step sintering yields MXene / carbon composite materials, which greatly simplifies the synthesis steps and reduces the reaction energy consumption.

[0061] The technical solution of the present invention has been illustrated above through specific embodiments. It should be understood that the one or more steps mentioned in the present invention do not preclude the existence of other methods and steps before or after the combined steps, or that other methods and steps may be inserted between these explicitly mentioned steps. It should also be understood that these examples are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise stated, the numbering of each method step is only for the purpose of identifying each method step, and not for limiting the order of each method or limiting the scope of the invention. Changes or adjustments to their relative relationships, without substantial changes to the technical content, can also be considered within the scope of the present invention.

[0062] The raw materials and instruments used in the examples are not specifically limited in their source; they can be purchased from the market or prepared using conventional methods well known to those skilled in the art. The graphene in the examples was prepared by laboratory personnel using expanded graphite as raw material and an airflow milling method.

[0063] The test method for the absorption performance in the embodiment is as follows: First, paraffin wax and the sample are weighed in a mass ratio of 1:1, heated to 60°C to melt the paraffin wax, and then the sample to be tested is added to mix it thoroughly and evenly in ultrasound. After cooling, the mixed sample is placed into a specific ring mold and pressed into a ring-shaped test sample with a thickness of about 2~3mm. Then, its electromagnetic parameters are tested using a vector network analyzer.

[0064] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.

Claims

1. A method for preparing an MXene / carbon composite material, characterized in that, The preparation method includes the following steps: heating a transition metal element, a carbon material, and a halide or a halide gas to a reaction temperature and holding it at that temperature for a predetermined time, so that MXene grows on the carbon material to obtain the MXene / carbon composite material. The transition metal is selected from one or more of the following: Ti, V, Ta, W, Zr, and Mo; The carbon material is selected from one or more of flake graphite, expanded graphite, and graphene.

2. The preparation method according to claim 1, characterized in that, The halide is selected from HCl, HBr or HI; And / or, the halogen gas is selected from Cl2, Br2 or I2.

3. The preparation method according to claim 1 or 2, characterized in that, The reaction temperature is between 650 and 850°C; And / or, the heat preservation time is between 1 minute and 24 hours; And / or, the chemical formula of the MXene is M2XT x Or M2X, where M represents a transition metal element; X represents carbon, and T represents... x The surface represents a surface containing functional groups, including at least one of Cl, Br, and I.

4. The preparation method according to any one of claims 1 to 3, characterized in that, The solid product obtained after the reaction is dispersed in a non-aqueous solvent, and impurities are separated by precipitation or centrifugation.

5. The preparation method according to claim 4, characterized in that, The non-aqueous solvent is selected from one or more of propylene carbonate, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, N,N-dimethylformamide, N-methylformamide, and isopropanol.

6. The preparation method according to claim 1, characterized in that, The transition metal element is titanium powder; And / or, the halogen hydride is hydrogen chloride.

7. An MXene / carbon composite material obtained by the preparation method according to any one of claims 1 to 6.

8. The MXene / carbon composite material as described in claim 7, characterized in that, The mass content of carbon material in the MXene / carbon composite material ranges from 1% to 99%.

9. Use of the MXene / carbon composite material as described in claim 7 or 8 for microwave absorption.

10. A microwave absorbing film or coating, characterized in that, include: The MXene / carbon composite material obtained by the preparation method according to any one of claims 1 to 6; Alternatively, the MXene / carbon composite material as described in claim 7 or 8.

11. A coating, characterized in that, The coating contains the MXene / carbon composite material as described in claim 7 or 8.

12. An electronic device, characterized in that, The electronic device is provided with the microwave absorbing film or coating as described in claim 10.

Citation Information

Patent Citations

  • MXene material taking Cl as surface group as well as preparation method and application of MXene material

    CN109437177A

  • Method for growing MXene material by using molten salt method and application of MXene material

    CN117105226A

  • One-dimensional MXene material as well as preparation method and application thereof

    CN117985716A